Method for measuring content of components in high-magnesium zinc alloy

The direct reading spectrometer determines the content of each element in the high-magnesium zinc alloy, and solves the problem that the existing technology cannot determine the content of magnesium element in the high-magnesium zinc alloy by more than 0.5%, and accurately determines various elements and improves the analysis precision degree and reliability.

CN119290823APending Publication Date: 2025-01-10YUNNAN CHIHONG RESOURCE COMPREHENSIVE UTILIZATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411456486.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing zinc alloy analysis methods cannot effectively determine the content of each element in high-magnesium zinc alloys with a magnesium content greater than 0.5%.

Method used

Direct reading spectrometer is used to determine the content of each element in high-magnesium zinc alloy. By preparing standards and setting appropriate excitation parameters, selecting appropriate analysis lines and reference lines, drawing working curves, and measuring spectral intensity values ​​to determine element content.

Benefits of technology

Accurate measurement of the magnesium element content in the range of 0.005%-10.0%, and the content of Al, Fe, Pb, Cd, Sn, and Cu elements can be accurately measured, thereby improving the measurement precision and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290823A_ABST
    Figure CN119290823A_ABST
Patent Text Reader

Abstract

The invention relates to a method for determining the content of components in a high-magnesium zinc alloy. The method comprises the following steps: preparing a high-magnesium-zinc alloy standard product, setting direct-reading spectrometer excitation parameters of all elements, drawing a working curve of all the elements, exciting a high-magnesium-zinc alloy sample by using the direct-reading spectrometer, measuring the spectral intensity value of all the elements, and obtaining the content of all the elements according to the working curve. According to the scheme provided by the invention, the contents of seven elements such as Al element, Mg element, Fe element, Pb element, Cd element, Sn element and Cu element in the high-magnesium zinc alloy with the magnesium element content greater than 0.5% can be accurately measured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of element analysis and testing methods for alloy materials, and in particular to a method for determining the content of components in a high-magnesium-zinc alloy. Background Art

[0002] The national standard GB / T 26042-2010 "Analysis of zinc and zinc alloys - Photoelectric emission spectrometry" specifies the photoelectric emission spectrometry analysis method for the content of lead, cadmium, iron, copper, tin, aluminum and magnesium in zinc and zinc alloys, where the determination range of magnesium is 0.005%-0.10%. The national standard GB-T 12689.12-2004 "Chemical analysis method of zinc and zinc alloys - Determination of lead, cadmium, iron, copper, tin, aluminum, arsenic, antimony, magnesium, lanthanum and cerium - Inductively coupled plasma - optical emission spectrometry" specifies the determination method for the content of lead, cadmium, iron, copper, tin, aluminum, arsenic, antimony, magnesium, lanthanum and cerium in zinc and zinc alloys, where the determination range of magnesium is 0.005%-0.50%. With the rapid development of zinc-aluminum-magnesium alloys in photovoltaics, automobiles, animal husbandry and other fields, domestic companies have developed high-magnesium zinc alloys with magnesium content >0.5%. However, the "Analysis Method of Zinc and Zinc Alloys - Photoelectric Emission Spectrometry" and the "Chemical Analysis Method of Zinc and Zinc Alloys - Determination of Lead, Cadmium, Iron, Copper, Tin, Aluminum, Arsenic, Antimony, Magnesium, Lanthanum and Cerium - Inductively Coupled Plasma-Emission Spectrometry" cannot determine high-magnesium zinc alloys with magnesium content greater than 0.5%.

[0003] Therefore, it is necessary to provide a method for simply and quickly determining the content of each element in a high-magnesium-zinc alloy with a magnesium content greater than 0.5%. Summary of the invention

[0004] In order to solve or partially solve the problems existing in the related art, the present application provides a method for determining the content of components in a high-magnesium-zinc alloy, which can determine the content of each element in a high-magnesium-zinc alloy with a magnesium content greater than 0.5%.

[0005] The present application provides a method for determining the content of components in a high magnesium-zinc alloy, comprising the following steps:

[0006] 1) Preparation of high magnesium zinc alloy standard;

[0007] The content ranges of various elements in the high magnesium zinc alloy are as follows: Mg element content is 0.005%-10.0%, Al element content is 0.0002%-10.0%, Fe element content is 0.0025%-0.05%, Pb element content is 0.0012%-0.02%, Cd element content is 0.0005%-0.02%, Sn element content is 0.0005%-0.02%, and Cu element content is 0.0005%-0.02%;

[0008] 2) Set the direct reading spectrometer excitation parameters of each element. The analysis line and reference line of each element are:

[0009] Select spectral lines according to the range of elements with different contents: select highly sensitive analytical lines for low-content elements, select sub-sensitive lines for higher-content elements, and select spectral lines close to the analytical lines for reference lines.

[0010] When the Al content is 0.002%-1.0%, the analysis line is 396.2nm, and the reference line is Zn472.2nm; when the Al content is 1.0%-5.0%, the analysis line is 309.3nm, and the reference line is Zn307.6; when the Al content is 5.0%-10.0%, the analysis line is 308.2nm, and the reference line is Zn303.6;

[0011] The elemental analysis line of Mg is 279.1nm, and the reference line of Zn is 196.9nm;

[0012] The Fe element analysis line is 372.2nm, and the reference line is Zn303.6nm;

[0013] The element analysis line of Pb is 405.8nm, and the reference line is Zn472.2nm;

[0014] The elemental analysis line of Cd is 228.8nm, and the reference line of Zn is 196.9nm;

[0015] The Sn element analysis line is 317.5nm, and the reference line is Zn472.2nm;

[0016] The elemental analysis line of Cu is 223.0nm, and the reference line of Zn is 196.9nm;

[0017] 3) Draw the working curve of each element;

[0018] 4) Use a direct reading spectrometer to excite the high magnesium-zinc alloy sample, measure the spectral intensity value of each element, and obtain the content of each element according to the working curve in step 4).

[0019] Optionally, in step 2), the flushing time is 2 s, the pre-combustion time is 10 s, and the exposure time is 4 s.

[0020] Optionally, the preparation method of the zinc-nickel alloy standard in step 1) is:

[0021] The preparation method of a high magnesium zinc alloy standard product with an Al content of 0.002%-5.0% is as follows: a zinc ingot, an aluminum ingot, an iron sheet and a cathode copper are melted, the temperature is lowered to 550-600° C., a magnesium ingot, a lead ingot, a cadmium ingot and a tin ingot are added, and the high magnesium zinc alloy standard product is obtained after stirring and melting for 10-20 minutes;

[0022] The preparation method of a high-magnesium-zinc alloy standard product with an Al element content of 5.0%-10.0% is as follows: a zinc ingot, an aluminum ingot, an iron sheet and a cathode copper are melted respectively; the molten aluminum ingot, the iron sheet and the cathode copper are added to the molten zinc ingot, stirred and melted, the temperature is lowered to 500-550°C, a magnesium ingot, a lead ingot, a cadmium ingot and a tin ingot are added, stirred and melted, and a high-magnesium-zinc alloy standard product is obtained after 10-20 minutes.

[0023] The technical solution provided by this application may have the following beneficial effects:

[0024] Although the prior art can determine the contents of aluminum and magnesium in aluminum-magnesium alloys with a magnesium content of 0.005%-10%, this method usually requires the use of mixed acids such as hydrochloric acid, nitric acid and nitric acid to dissolve the sample, and the type and concentration of the acid will affect the accuracy of the determination; however, the present application prepares a high-magnesium-zinc alloy with a Mg content of 0.005%-10.0%, sets the excitation parameters of the direct-reading spectrometer for the Mg element to: the analysis line is 279.1nm, the exposure stage is exposure 1, the reference line is Zn3 196.9nm, the flushing time is 2S, the pre-combustion time is 10S, and the exposure time is 4S, and the high-magnesium-zinc alloy is directly measured, and the Mg content in the high-magnesium-zinc alloy with a Mg content in the range of 0.005%-10.0% can be accurately determined.

[0025] By setting the analysis lines, exposure stages, reference lines, flushing time, pre-burning time and exposure time of Al, Fe, Pb, Cd, Sn and Cu elements, the Al content in high magnesium-zinc alloys with an Al content in the range of 0.002%-10.0% can be accurately determined, the Fe content in high magnesium-zinc alloys with an Fe content in the range of 0.0025%-0.05% can be accurately determined, the Pb content in high magnesium-zinc alloys with a Pb content in the range of 0.0012%-0.02% can be accurately determined, and the Cd, Sn and Cu contents in high magnesium-zinc alloys with Cd, Sn and Cu contents in the range of 0.0005%-0.02% can be accurately determined.

[0026] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The above and other objects, features and advantages of the present application will become more apparent through a more detailed description of exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0028] Figure 1 It is a schematic diagram of the Al element working curve shown in this application;

[0029] Figure 2 It is a schematic diagram of the Mg element working curve shown in this application. DETAILED DESCRIPTION

[0030] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0031] Example 1: Preparation of high magnesium zinc alloy standard

[0032] The preparation method of a high magnesium zinc alloy standard product with an Al content of 0.002%-5.0% is as follows: a zinc ingot, an aluminum ingot, an iron sheet and a cathode copper are melted in a medium frequency induction furnace at a temperature of 650-700° C., after melting, the temperature is lowered to 550-600° C., and a magnesium ingot, a lead ingot, a cadmium ingot and a tin ingot are added, and after stirring and melting, a high magnesium zinc alloy standard product is obtained after 10-20 minutes;

[0033] The preparation method of a high-magnesium-zinc alloy standard product with an Al element content of 5.0%-10.0% is as follows: a zinc ingot is melted in a medium-frequency induction furnace at a temperature of 450-500°C; an aluminum ingot, an iron sheet and a cathode copper are melted in a high-precision automatic temperature control cabinet at a temperature of 700°C; the molten aluminum ingot, the iron sheet and the cathode copper are added to the molten zinc ingot, stirred and fused, the temperature is lowered to 500-550°C, a magnesium ingot, a lead ingot, a cadmium ingot and a tin ingot are added, stirred and melted, and a high-magnesium-zinc alloy standard product is obtained after 10-20 minutes.

[0034] The amount of each raw material added is shown in Table 1:

[0035] Table 1 The amount of each raw material added for high magnesium zinc alloy standard product

[0036]

[0037] According to the above high magnesium zinc alloy standard preparation method, 8 high magnesium zinc alloy standards were prepared, and the content of each element is shown in Table 2.

[0038] Table 2 Content of each element in high magnesium zinc alloy standard

[0039]

[0040] Example 2: Verification of the effect of excitation parameters of direct reading spectrometer

[0041] Select the spectrum line according to the range of elements with different contents: select the high-sensitivity analysis spectrum line for low-content elements, select the sub-sensitive line for high-content elements, and select the spectrum line close to the analysis spectrum line for the reference line. In this application, when the Al content is 0.002%-1.0%, the analysis line is 396.2nm, and the reference line is Zn472.2nm; when the Al content is 1.0%-5.0%, the analysis line is 309.3nm, and the reference line is Zn307.6; when the Al content is 5.0%-10.0%, the analysis line is 308.2nm, and the reference line is Zn303.6;

[0042] The other conditions remained unchanged, only the flushing time was changed, and the high magnesium-zinc alloy standard numbered MD J21143 was excited 11 times. The results (Table 3) showed that when the flushing time was >2S, the RSD value of the light intensity ratio of Al and Mg was <2%, and the data was stable. In order to save analysis time, the flushing time was selected as 2S.

[0043] Table 3 Light intensity ratio data at different flushing times

[0044]

[0045] When other conditions remain unchanged and only the pre-combustion time is changed, the high magnesium-zinc alloy standard of MD J21143 is excited. The results (Table 4) show that when the pre-combustion time is greater than 10S, the RSD value of the light intensity ratio of Al and Mg is less than 2%, and the data is stable. In order to save time and reduce sample consumption, the pre-combustion time is selected as 10S.

[0046] Table 4 Light intensity ratio data for different pre-combustion time

[0047]

[0048]

[0049] With other conditions unchanged, only the exposure time was changed to excite the high magnesium-zinc alloy standard MD J21143. The results (Table 5) showed that when the exposure time was >4S, the RSD value of the light intensity ratio of Al and Mg was <2%, and the data was stable. In order to save time and reduce sample consumption, the exposure time was selected to be 4S each time.

[0050] Table 5 Light intensity ratio data for different pre-combustion time

[0051]

[0052]

[0053] Example 3: Drawing a working curve

[0054] Set the direct reading spectrometer excitation parameters for each element;

[0055] The excitation parameters of the direct reading spectrometer for the Mg element are: the analysis line is 279.1nm, the exposure stage is exposure 3, the reference line is Zn3 196.9nm, the flushing time is 2S, the pre-burning time is 10S, and the exposure time is 10S;

[0056] When the Al element content is 0.002%-1.0%, the analysis line is 396.2nm, the exposure stage is exposure 1, and the reference line is Zn1 472.2nm; when the Al element content is 1.0%-5.0%, the analysis line is 309.3nm, the exposure stage is exposure 3, and the reference line is Zn3 307.6; when the Al element content is 5.0%-10.0%, the analysis line is 308.2nm, the exposure stage is exposure 3, the reference line is Zn3 303.6, the flushing time is 2S, the pre-combustion time is 10S, and the exposure time is 10S.

[0057] The excitation parameters of the direct reading spectrometer for the Fe element are: analysis line at 372.2 nm, exposure stage at exposure 1, reference line at Zn1 303.6 nm, flushing time at 2 s, pre-burning time at 10 s, and exposure time at 10 s.

[0058] The excitation parameters of the direct reading spectrometer for the Pb element are: analysis line 405.8 nm, exposure stage exposure 1, reference line Zn1 472.2 nm, flushing time 2 s, pre-combustion time 10 s, and exposure time 10 s.

[0059] The excitation parameters of the direct reading spectrometer for the Cd element are: analysis line 228.8 nm, exposure stage exposure 3, reference line Zn3 196.9 nm, flushing time 2 s, pre-burning time 10 s, and exposure time 10 s.

[0060] The excitation parameters of the direct reading spectrometer for Sn element are: analysis line is 317.5nm, exposure stage is exposure 1, reference line is Zn1 472.2nm, flushing time is 2S, pre-burning time is 10S, and exposure time is 10S.

[0061] The excitation parameters of the direct reading spectrometer for the Cu element are: analysis line 223.0 nm, exposure stage exposure 4, reference line Zn4 196.9 nm, flushing time 2 s, pre-burning time 10 s, and exposure time 10 s.

[0062] Use a direct reading spectrometer to excite the high magnesium zinc alloy standard sample, and draw the working curve of each element with the spectral intensity value of each element as the horizontal axis and the content of each element in the standard sample as the vertical axis. Figure 1 , Figure 2 shown.

[0063] Example 4

[0064] High-magnesium-zinc alloy samples with high magnesium content and low magnesium content were selected for precision tests. After 11 parallel measurements, the results were read from the established working curve. The results are shown in Tables 6 and 7.

[0065] Table 6 Precision test results of high magnesium zinc alloy samples with high magnesium content

[0066]

[0067] Table 7 Precision test results of high magnesium zinc alloy samples with low magnesium content

[0068]

[0069]

[0070] It can be seen from Table 6 that when the magnesium content in the high magnesium zinc alloy sample is greater than 7%, the range of the Al element content is 0.090%, the standard deviation is 0.034%, and the relative standard deviation (RSD) is 0.017%. The range of the Fe element content is 0.0004%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.023%; the range of the Pb element content is 0.0002%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.032%, and the range of the Cd element content is The range of Sn element content is 0.0002%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.052%. The range of Cu element content is 0.0002%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.091%. The range of Cu element content is 0.0002%, the standard deviation is 0.0002%, and the relative standard deviation (RSD) is 0.081%. The range of Mg element content is 0.140%, the standard deviation is 0.045%, and the relative standard deviation (RSD) is 0.006%.

[0071] It can be seen from Table 7 that when the magnesium content in the high magnesium zinc alloy sample is less than 7%, the range of the Al element content in the test results is 0.11%, the standard deviation is 0.034%, and the relative standard deviation (RSD) is 0.004%. The range of the Fe element content is 0.0007%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.024%. The range of the Pb element content is 0.0002%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.030%. The range of the Cd element content is The range of Sn element content is 0.0003%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.087%. The range of Cu element content is 0.0002%, the standard deviation is 0.0001%, and the relative standard deviation (RSD) is 0.092%. The range of Mg element content is 0.07%, the standard deviation is 0.028%, and the relative standard deviation (RSD) is 0.009%.

[0072] It can be seen from the above table that the method for determining the content of components in high magnesium-zinc alloys in this application has good repeatability and can meet the analysis requirements.

[0073] Example 5

[0074] The high magnesium zinc alloy samples were subjected to composition analysis using the test method of the present application and the chemical method.

[0075] The results of comparison with the method of the present application are shown in Table 8.

[0076] Table 8 Comparison of the test method of this application and the results of the chemical method

[0077]

[0078] As can be seen from Table 8, the sample results measured by the test method of the present application are in good agreement with the results measured by the chemical method. The present application has high accuracy and reliability.

[0079] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for determining the content of components in a high magnesium-zinc alloy, characterized in that: The following steps are involved: 1) Preparation of high magnesium zinc alloy standard; The content ranges of the elements in the high magnesium zinc alloy are as follows: Mg element content is 0.005%-10.0%, Al element content is 0.002%-10.0%, Fe element content is 0.0025%-0.05%, Pb element content is 0.0012%-0.02%, Cd element content is 0.0005%-0.02%, Sn element content is 0.0005%-0.02%, and Cu element content is 0.0005%-0.02%; 2) Set the direct reading spectrometer excitation parameters of each element. The analysis line and reference line of each element are: When the Al content is 0.002%-1.0%, the analysis line is 396.2nm, and the reference line is Zn472.2nm; when the Al content is 1.0%-5.0%, the analysis line is 309.3nm, and the reference line is Zn307.6; when the Al content is 5.0%-10.0%, the analysis line is 308.2nm, and the reference line is Zn303.6; The elemental analysis line of Mg is 279.1nm, and the reference line of Zn is 196.9nm; The Fe element analysis line is 372.2nm, and the reference line is Zn303.6nm; The element analysis line of Pb is 405.8nm, and the reference line is Zn472.2nm; The elemental analysis line of Cd is 228.8nm, and the reference line of Zn is 196.9nm; The Sn element analysis line is 317.5nm, and the reference line is Zn472.2nm; The elemental analysis line of Cu is 223.0nm, and the reference line of Zn is 196.9nm; 3) Draw the working curve of each element; 4) Using a direct reading spectrometer to excite the high magnesium-zinc alloy sample, measuring the spectral intensity value of each element, and obtaining the content of each element according to the working curve described in step 4).

2. The method according to claim 1, characterized in that: In the step 2), the flushing time is 2 seconds, the pre-combustion time is 10 seconds, and the exposure time is 4 seconds.

3. The method according to claim 1, characterized in that The preparation method of the high magnesium zinc alloy standard in step 1) is: The preparation method of a high magnesium zinc alloy standard product with an Al content of 0.002%-5.0% is as follows: a zinc ingot, an aluminum ingot, an iron sheet and a cathode copper are melted, the temperature is lowered to 550-600° C., a magnesium ingot, a lead ingot, a cadmium ingot and a tin ingot are added, and the high magnesium zinc alloy standard product is obtained after stirring and melting for 10-20 minutes; The preparation method of a high-magnesium-zinc alloy standard product with an Al element content of 5.0%-10.0% is as follows: a zinc ingot, an aluminum ingot, an iron sheet and a cathode copper are melted respectively; the molten aluminum ingot, the iron sheet and the cathode copper are added to the molten zinc ingot, stirred and melted, the temperature is lowered to 500-550°C, a magnesium ingot, a lead ingot, a cadmium ingot and a tin ingot are added, stirred and melted, and a high-magnesium-zinc alloy standard product is obtained after 10-20 minutes.